PENGARUH PENGETAHUAN PERPAJAKAN DAN SANKSI PAJAK TERHADAP KEPATUHAN WAJIB PAJAK DI KOTA PEKALONGAN - Umi Marifah; Imahda Khoiri Furqon (Jurnal Ekonomi & Bisnis, 2023)
This research aims to determine the influence of public knowledge regarding taxation and tax sanctions on taxpayer compliance in the city of Pekalongan. This research uses qualitative methods by collecting data that emphasizes the people of Pekalongan city, in order to obtain accurate information in this research. The results of the research conclude that the knowledge of taxation and tax sanctions have a very large influence on taxpayer compliance in Pekalongan City. Knowledge of taxation is an important element for all people to know clearly what taxation is like. Apart from that, the benefits of taxation knowledge are very important in life because with taxes we can help the development of the country because one of the largest state revenues comes from taxes. Sanctions against the public are very much needed to create order in the world of taxation. Apart from that, the government's outreach to the public must be carried out frequently as a reminder to ensure taxpayer compliance.